Nε-lysine acetylation of the histone-like protein HBsu influences antibiotic survival and persistence in Bacillus subtilis - Carr, Rachel A.; Tucker, Trichina; Newman, Precious M.; Jadalla, Lama; Jaludi, Kamayel; Reid, Briana E.; Alpheaus, Damian N.; Korrapati, Anish; Pivonka, April E.; Carabetta, Valerie J. (Frontiers in Microbiology, 2024)
N ε -lysine acetylation is recognized as a prevalent post-translational modification (PTM) that regulates proteins across all three domains of life. In Bacillus subtilis, the histone-like protein HBsu is acetylated at seven sites, which regulates DNA compaction and the process of sporulation. In Mycobacteria, DNA compaction is a survival strategy in response antibiotic exposure. Acetylation of the HBsu ortholog HupB decondenses the chromosome to escape this drug-induced, non-growing state, and in addition, regulates the formation of drug-tolerant subpopulations by altering gene expression. We hypothesized that the acetylation of HBsu plays similar regulatory roles. First, we measured nucleoid area by fluorescence microscopy and in agreement, we found that wild-type cells compacted their nucleoids upon kanamycin exposure, but not exposure to tetracycline. We analyzed a collection of HBsu mutants that contain lysine substitutions that mimic the acetylated (glutamine) or unacetylated (arginine) forms of the protein. Our findings indicate that some level of acetylation is required at K3 for a proper response and K75 must be deacetylated. Next, we performed time-kill assays of wild-type and mutant strains in the presence of different antibiotics and found that interfering with HBsu acetylation led to faster killing rates. Finally, we examined the persistent subpopulation and found that altering the acetylation status of HBsu led to an increase in persister cell formation. In addition, we found that most of the deacetylation-mimic mutants, which have compacted nucleoids, were delayed in resuming growth following removal of the antibiotic, suggesting that acetylation is required to escape the persistent state. Together, this data adds an additional regulatory role for HBsu acetylation and further supports the existence of a histone-like code in bacteria.